Endoscopic submucosal dissection with double clip and rubber band traction for residual or locally recurrent colonic lesions after previous endoscopic mucosal resection - Faller, Julien; Jacques, Jérémie; Oung, Borathchakra; Legros, Romain; Rivory, Jérôme; Subtil, Fabien; Saurin, Jean-Christophe; Robinson, Philip; Ponchon, Thierry; Pioche, Mathieu (Endoscopy, 2020)
Background Endoscopic submucosal dissection (ESD) of residual or locally recurrent (RLR) colonic lesions after previous endoscopic mucosal resection (EMR) is an attractive but challenging technique. The present study aimed to evaluate the effectiveness and safety of ESD with double clip and rubber band traction (DCT-ESD) of RLR colonic lesions.Methods We retrospectively analyzed all consecutive DCT-ESD procedures for RLR colonic lesions (rectum excluded) performed in two French centers. The frequency of en bloc and R0 resections, procedure speed, additional surgery, and complications were evaluated. R0 resection was also used to investigate the learning curve.Results Among the 53 resections, 49 (92.5 %) were performed en bloc and 42 (79.2 %) achieved R0. The median procedure speed was 21 mm2/min. There were four (7.5 %) intraoperative perforations and one delayed bleeding; these were successfully treated endoscopically. There was no salvage surgery for complications. The R0 rate increased from 16/26 (61.5 %) for the first 26 procedures to 26/27 (96.3 %, P = 0.002) for the last 27 procedures.Conclusions DCT-ESD appears to be a safe and effective treatment for RLR colonic lesions after EMR.